2017
DOI: 10.1038/mp.2017.143
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine abuse impairs motor cortical plasticity and function

Abstract: Exposure to addictive drugs triggers synaptic plasticity in reward-related brain regions, such as the midbrain, nucleus accumbens and the prefrontal cortex. Effects of chronic drug exposure on other brain areas have not been fully investigated. Here, we characterize synaptic plasticity in motor cortex after methamphetamine self-administration in rats. We show that this causes a loss of corticostriatal plasticity in rat brain slices and impaired motor learning in the rotarod task. These findings are paralleled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 34 publications
4
47
0
Order By: Relevance
“…The original TBS neurophysiological study employed 80% active MT targeting the primary motor cortex (Huang et al, 2005), while other clinical trials have also tried 120% resting MT of the DLPFC demonstrating both safety and tolerability . Our previous study has shown that TBS (single session/80% motor threshold) over the motor cortex cannot induce cerebral plasticity, which indicates that neuroplasticity is supposed to be altered in methamphetamine users (Huang et al, 2017). The TBS-related plasticity and behavioral change might highly depend on the intensity, the total number of pulses, the number of sessions, and the stimulating site.…”
Section: Discussionmentioning
confidence: 99%
“…The original TBS neurophysiological study employed 80% active MT targeting the primary motor cortex (Huang et al, 2005), while other clinical trials have also tried 120% resting MT of the DLPFC demonstrating both safety and tolerability . Our previous study has shown that TBS (single session/80% motor threshold) over the motor cortex cannot induce cerebral plasticity, which indicates that neuroplasticity is supposed to be altered in methamphetamine users (Huang et al, 2017). The TBS-related plasticity and behavioral change might highly depend on the intensity, the total number of pulses, the number of sessions, and the stimulating site.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies on a larger scale will be performed. It will be also interesting to quantify the motor cortical changes following training with non-invasive measurement approaches, for instance ( Huang et al, in press ; Shen et al, 2017 ; Zhou et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, these models assume that other direct and indirect costs of MDD were the same for both medication and rTMS treatment. These include the direct costs of concomitant treatment for alcohol and drug abuse [ 53 , 54 , 55 ], sleep and mood disorders, anxiety, and Attention-Deficit Hyperactivity Disorder (ADHD), and sexual disorders, as well as the indirect costs of disability [ 56 ] and suicide [ 57 ]. These models also assume other direct non-depression costs are the same which include: non-depression related prescription drugs (@ $1,440 /year) [ 31 ] and; non-mental health provider visits (@$7,700/year) [ 31 ].…”
Section: Limitationsmentioning
confidence: 99%